Medium chain fatty acids production from simple substrate and waste activated sludge with ethanol as the electron donor. (November 2021) - He, Junguo; Li, Lin; Zhang, Jie; Wu, Xuewei; Li, Biqing; Tang, Xia
Abstract: Production of MCFAs (Medium-chain fatty acids) from simple substrate (i.e., ethanol and acetate) and WAS with chain elongation microbiome was investigated in this study. The results showed that rapid production of MCFAs was observed when simple substrate was utilized. 1889 mg/L of caproate and 3434 mg/L of butyrate were achieved after 10 d's reaction. H2 proportion in the headspace could reach as high as 10.1% on day 8 and then declined quickly. However, when WAS was used, the bacterial consortia was not able to hydrolyze WAS efficiently, which resulted in poor MCFAs production performance. Presence of ethanol could improve the hydrolysis process to a limited degree, which resulted in solubilization of a small fraction of protein and carbohydrate. Around 33.8% and 36.9% of the total detected electrons on day 6 in the 50 mM and 100 mM tests were extracted from WAS respectively. Those results indicate that the chain elongation microbial consortia tended to receive electrons form ethanol directly other than the complex WAS. Highlights: Better MCFAs production performance with simple substrate than WAS was observed. Ethanol can improve hydrolysis process of WAS. Bacteria were inclined to extract reducing equivalent from ethanol other than WAS. 33.8% and 36.9% of the detected electrons on day 6 were extracted from WAS.